An initial analysis of the UK Medical Cannabis Registry: Outcomes analysis of first 129 patients - Simon Erridge; Oliver Salazar; Michal Kawka; Carl Holvey; Ross Coomber; Azfer Usmani; Mohammed Sajad; Sushil Beri; Jonathan Hoare; Shaheen Khan; Mark W. Weatherall; Michael Platt; et al. (Wiley, 2021)
Abstract Aim Cannabis‐based medicinal products (CBMPs) are prescribed with increased frequency, despite a paucity of high‐quality randomized controlled trials. The aim of this study is to analyze the early outcomes of the first series of patients prescribed CBMPs in the UK with respect to effects on health‐related quality of life and clinical safety. Methods A prospective case series was performed using the UK Medical Cannabis Registry. Primary outcomes were change in patient‐reported outcomes measures (EQ‐5D‐5L, General Anxiety Disorder‐7 (GAD‐7) and Single‐Item Sleep Quality Scale (SQS)) at 1 and 3 months from baseline. The secondary outcome was the incidence of adverse events. Statistical significance was defined by a P‐value <.050. Results There were 129 patients included in the final analysis with a mean age of 46.23 (±14.51) years. The most common indication was chronic pain of undefined etiology (n = 48; 37.2%). The median initial cannabidiol and (−)‐trans‐Δ⁹‐tetrahydrocannabinol daily dose was 20.0 mg (Range: 0.0‐768.0 mg) and 3.9 mg (Range: 0.0‐660.0 mg), respectively. Statistically significant improvements in health‐related quality of life were demonstrated at 1 and 3 months in GAD‐7, SQS, EQ‐5D‐5L pain and discomfort subscale, EQ‐5D‐5L anxiety and depression subscale, EQ‐VAS and EQ‐5D‐5L index values(P < .050). There were 31 (24.03%) total reported adverse events. Conclusion This study suggests that CBMP therapy may be associated with an improvement in health‐related quality‐of‐life outcomes as self‐reported by patients. CBMPs are also demonstrated to be relatively safe in the short to medium‐term. These findings must be treated with caution given the limited scope of this initial analysis, with no placebo or an active comparator, with further research required.